Interaksi Sosial Lansia dalam Aktivitas Harian di Sentra “Gau Mabaji” Kabupaten Gowa - Nurannisa Lumanto; Najamuddin Najamuddin; Supriadi Torro (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze: (1) the forms of social interaction among the elderly at the